A highly complex stingless bee propolis: Composition and influence of the period of collection. Issue 2 (13th February 2022) - Negri, Giuseppina; Salatino, Antonio; Pereira, Leonardo L Regnier; Salatino, Maria Luiza Faria; do Nascimento, Roberto Manoel; Mendonça, Ronaldo Zucatelli
Abstract: Background: Stingless bees or meliponines (family Apidae, subfamily Meliponinae, tribe Meliponini) are eusocial bees from tropical and subtropical regions. Propolis of Scaptotrigona aff. postica (Latreille, 1807) is used in the state of Maranhão (Northeast Brazil) in ointments to treat tumors and wounds. Samples of propolis of S . aff. postica (Apidae, Meliponini) were collected monthly from an apiary located in Barra do Corda (state of Maranhão, Northeast Brazil). Extracts of the 12 samples were obtained with 80% ethanol. Constituents of the samples were characterized by high performance liquid chromatography coupled to photodiode array detector and electrospray ionization tandem mass spectrometry analysis, amounting to 100 substances. Results: Representatives of several classes of secondary metabolites were characterized, including benzoic and cinnamic acids, flavonoids (chalcones, flavone‐ C ‐glycosides, flavonol aglycones, and glycosides), alkyl and alkenyl resorcinols, xanthones, diterpenes, cycloartane‐type triterpenoids, pentacyclic triterpenoids, pyrrolizidine alkaloids, and hydroxycinnamic acid amides (HCAAs). Considerable qualitative differences in chemical composition among samples were observed, depending on the year period of collection. Principal Coordinate Analysis recognized three distinct year periods (Jan–Mar, April–Sep, Oct–Dec) according to the corresponding chemical profiles. Conclusion: Compared with previous studies, the present work indicates that considerable differences in chemical composition occur also from year to year. Contrary to most propolis types reported so far, which derive exclusively or mostly from a single botanical source, the propolis from Barra do Corda seemingly depends on several resin sources. It is suggested that chalcones and flavonols stem from Mimosa tenuiflora (Mimosoideae); resorcinols, xanthones, and cycloartane‐type triterpenoids, from fruits of Mangifera indica (Anacardiaceae); pyrrolizidine alkaloids, possibly from some Crotalaria species (Faboideae); HCAAs probably originate from pollen contaminating the propolis samples. The propolis of S . aff. postica poses challenges and possibilities of study for apicultural researchers, chemists, and pharmacologists.